Effect of Heavy Machine Traffic on Soil CO2 Concentration and Efflux in a Pinus koraiensis Thinning Stand - Ikhyun Kim (MDPI AG, 2021)
Mechanized timber harvesting is cost efficient and highly productive. However, mechanized harvesting operations are often associated with several environmental problems, including soil compaction and disturbance. Soil compaction impedes air circulation between the soil and atmosphere, which in turn results in increased concentrations of CO2 within soil pores. In this study, we investigated the impact of forest machine traffic on soil conditions to determine soil CO2 efflux (Fc), and soil CO2 concentrations (Sc). Field measurements included soil bulk density (BD), soil temperature (ST), soil water content (SWC), Fc, and Sc over a 3-year period at a specific thinning operation site (Hwacheon-gun) in the Gangwon Province of Korea. To assess the soil impacts associated with machine traffic, we established four machine-treatment plots (MT) characterized by different geographical and traffic conditions. The results revealed that BD, Sc, and SWC increased significantly on the disturbed track areas (p < 0.05). Furthermore, reduced soil Fc values were measured on the soil-compacted (machine disturbed) tracks in comparison with undisturbed (control) areas. Variations in BD, SWC, and Sc were significantly different among the four MT plots. Additionally, in comparison with undisturbed areas, lower Fc and higher Sc values were obtained in compacted areas with high soil temperatures.